Product improvement by using design for assembly : a case study on heavy duty staple gun - Muhamad Faiz, A Razak (2016)
This paper shows a detailed study to analyse the efficiency of Boothroyd Dewhurst Design for Assembly (DFA) method that was applied to improve the product design process. In today competitive world, companies try to cut down the manufacturing cost and at the same time increase their profit. In order to be a competent player in the market, the product should arrive into market within a short time and reasonable price. Assembly cost is one of the major operations in manufacturing but always ignored during designing stage. In this study, comparative analysis was done between original and alternative design. The design was done by using CATIA V5 software and analysed by using DFA software analysis to get the efficiency of original design. Then, by applying Boothroyd Dewhurst DFA method guideline, alternative design was generated and analysed using the same method to compare the effectiveness of this new alternative design. From the study, it was found that the design efficiency increased from 48.4% to 68.2% when Boothroyd Dewhurst DFA method was applied. The time of assemble also decreased from 248.83 seconds to 175.17 seconds per product. From the result, it was proven that this Boothroyd Dewhurst DFA method was able to improve the design in terms of design efficiency, product assemble time and labor cost. This method can be applied in manufacturing company in order to improve their design effectiveness.